IMPLEMENTASI KAIDAH-KAIDAH FIQHIYYAH DALAM ASURANSI - Fahmi Idris; SITI SOPIAH; Siti Hamidah; Firda Khoerunisa; Yudianto Achmad (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Apart from originating from the Qur'an and Hadith, sources of Islamic law, there are also ijma, qiyas, istihsan, maslahah mursalah, istishab, urf, syar'u man qablana, sadd az-zari'ah. There is a basis that is no less important, namely qawa'id fiqhiyyah which functions as the bass for the formation of law. The fiqhiyyah rule is the foundation that maslahah mursalah is the most appropriate to use as the basis for ushul fiqh as a solution to problems related to insurance. The rule of fiqh is one of the methods of taking law which is designed as a basis because this rule discusses issues related to religious rituals and social interaction. Therefore, a literature/literature study can describe or analyze research results but is not used to make broader conclusions. The data obtained is described using words or sentences so that it can become a discourse which is the conclusion of the data analysis. so that we do not only know the rules but know how to implement them in Islamic banking products.